Moving towards circular economy in agricultural sector: experimental farms in Guanajuato, Mexico - Cervantes, Gemma (2021)
: The agricultural sector is very important worldwide, in Latin America and Mexico, due to increasing population and therefore the need for food. But this sector works mainly as a linear production system, instead of a circular one. This causes the generation of large amount of waste, which can cause water, soil and, especially, atmospheric pollution if not disposed correctly. It is therefore essential to help agricultural systems to close the material cycle and thus reduce environmental impacts and obtain a higher performance in the system. This will help to knowing how to contribute to the circular economy in the agricultural sector. This article presents the study carried out with three experimental farms in the state of Guanajuato (Mexico). The farms were diagnosed qualitatively and quantitatively, the valuation of wastes already done in the farms was detected, and new valuations were proposed for each of them. An eco-industrial agricultural network was proposed between the three farms, made up of 11 entities, 7 different industrial sectors, 8 existing synergies, 18 proposed synergies, 22 different recovered or reused waste. With this network, a solution is proposed for 8 of the 10 most problematic farm wastes and contributes to closing the material cycle in them. Criteria are also given to tend to the circular economy in the agricultural sector.